National identity profiles and support for the European Union. (June 2021) - Aichholzer, Julian; Kritzinger, Sylvia; Plescia, Carolina
Scholars have long recognized that national identity-related factors are among the strongest predictors of citizens' attitudes toward the European Union. But while some find that they reinforce support for the European Union, other scholars show that national identity undermines its support. In this article, we aim to disentangle this puzzle by studying how the national identity profiles of European citizens relate to support for the European Union across individuals and member states. To this end, we employ data from the International Social Survey Program 2013, by far the most extensive collection of survey questions on national identity, and the technique of latent class analysis. Our results show which specific configurations of national identity entail support, ambivalence or rejection of the European Union, their antecedents, and their variation across countries.